Quantitative analysis of multi-components by single marker—a rational method for the internal quality of Chinese herbal medicine - Chunsheng Zhu; Xiaoping Li; Bing Zhang; Zhijian Lin (Integrative Medicine Research)
In order to achieve the comprehensive quality control of Chinese herbal medicine (CHM), the conventional practice of selecting a single marker for testing has been gradually replaced by the determination of multiple active components based on the characteristics of the synergistic interaction of CHM and applicability of sophisticated analytical techniques. However, with a huge number of CHM in the market and more complex preparations, the limited availability of various standard substances for quantitative analysis has been a major bottleneck in realizing the goal. To overcome these uprising problems, quantitative analysis of multi-components by single marker (QAMS) was proposed and accepted as a new method to reflect the internal quality of CHM. In this review, the current knowledge about QAMS is systematically summarized, including the general content of QAMS, current status, and general procedure. Additionally, speculation is proposed about the future applications of QAMS approaches in the modernization and standardization of CHM.